2013
DOI: 10.1097/rli.0b013e31827b70f9
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Iodinated Contrast Agent Properties on Renal Kinetics and Oxygenation

Abstract: We identified a superior profile for the low-osmolar CAs compared with the iso-osmolar CAs regarding rapid excretion, short-term renal exposure, and renal oxygenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 41 publications
1
31
0
1
Order By: Relevance
“…The protective effect of LIPC on ischemia/reperfusion injury has been shown to be associated with activation of the reperfusion injury salvage kinases (RISK) pathway, in which PI3K/Akt and ERK1/2 signaling leads to the phosphorylation of glycogen synthase kinase-3β (GSK-3β) [10,11]. In addition, several studies [12][13][14] have shown that hypoperfusion and hypoxia in the renal medulla occur within minutes after the injection of CM, and the kidney then suffers from subsequent reperfusion injury and reactive oxygen species (ROS) generation. We hypothesized that the RISK signaling pathway is involved in the renoprotection induced by LIPC.…”
Section: Introductionmentioning
confidence: 98%
“…The protective effect of LIPC on ischemia/reperfusion injury has been shown to be associated with activation of the reperfusion injury salvage kinases (RISK) pathway, in which PI3K/Akt and ERK1/2 signaling leads to the phosphorylation of glycogen synthase kinase-3β (GSK-3β) [10,11]. In addition, several studies [12][13][14] have shown that hypoperfusion and hypoxia in the renal medulla occur within minutes after the injection of CM, and the kidney then suffers from subsequent reperfusion injury and reactive oxygen species (ROS) generation. We hypothesized that the RISK signaling pathway is involved in the renoprotection induced by LIPC.…”
Section: Introductionmentioning
confidence: 98%
“…It can be affected by variations in R2 (= 1/T2) because, for example, of changes in water content [48]. Although the second BOLD MRI was done 24 h after contrast administration, we cannot exclude the possibility that contrast retention within the kidney could affect R2 [49]. Studies of water loading in normal volunteers demonstrated a change in cortical R2 of 0.72/s, while R2* fell by 1.36/s.…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…Here, the difference in CM osmolalities plays a major role (290 versus 796 mosmol/kg H 2 O) [29,32,41]. Non-reabsorbable CM diminish the osmotic gradient that drives tubular water resorption, thereby inducing osmodiuresis.…”
Section: Issn: 2380-0585mentioning
confidence: 99%
“…Please note that the very high creatinine clearance values for the first sampling period following CM (0-10 min, depicted as grey shadows) do not represent actual increases in glomerular filtration rate, but rely on the dead-space effect (see Results). [2,20,28,29,[32][33][34][35]. Hypoxia is part of a vicious circle that entails cellular damage, oxidative stress and vasoconstriction [2,28,29].…”
Section: Issn: 2380-0585mentioning
confidence: 99%
See 1 more Smart Citation